2010
DOI: 10.3343/kjlm.2010.30.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Prevalence of Human Parvovirus B19 DNA in Korean Plasmapheresis Donors

Abstract: -3.2×104 IU/mL) except for 1 donor (1.33×10 8 IU/mL). All the isolated B19V DNAs from 6 donors were identified as genotype I. Nine out of 10 B19V DNA positive donors also possessed anti-B19V IgG only or IgG and IgM. The prevalence of anti-B19V IgG was 60.1% (558/928). Conclusions :The prevalence of B19V DNA in Korean blood donors was not high and most donors also possessed neutralizing anti-B19V antibodies. Thus, the implementation of a B19V screening test for Korean blood donors does not appear to be imperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
5
4
0
Order By: Relevance
“…In our study, the prevalence of B19 DNA in healthy blood donors was 1.2%, which was compatible with data observed in some countries such as the USA (0.88%) . Nevertheless, this prevalence was higher than some countries such as Korea (0.1%), Belgium (0.2%), Germany and Austria (0.27%), and China (0.58 %) …”
Section: Discussionsupporting
confidence: 91%
“…In our study, the prevalence of B19 DNA in healthy blood donors was 1.2%, which was compatible with data observed in some countries such as the USA (0.88%) . Nevertheless, this prevalence was higher than some countries such as Korea (0.1%), Belgium (0.2%), Germany and Austria (0.27%), and China (0.58 %) …”
Section: Discussionsupporting
confidence: 91%
“…In previous studies performed among blood donors in the São Paulo state, the detected prevalence was between 0% and 1% ( n = 1 of 100 blood samples) . The rate of B19V DNA detection in South Brazil was similar to studies performed in blood donors from Ghana (1.3%) and Iran (1.2%) but higher than prevalences observed in other countries like Japan (0.01%), Korea (0.1%), China (0.06%‐0.58%); Germany, 0.66%, Denmark (0.006%), Portugal (0.18%), Netherlands (0.56%), and the United States (0.88%) . These differences could be due to geographic or seasonal differences of B19V circulation, and the sensitivity of the applied PCR detection methods …”
Section: Discussionsupporting
confidence: 70%
“…We detected a seroprevalence of 62.2% and the positivity of IgM was 0.06% in SANBS blood donors which is comparable with the seroprevalence in other reports . Varying PVB19 IgG prevalence has been reported ranging from 6% to 82.3% .…”
Section: Discussionsupporting
confidence: 88%
“…We detected a PVB19 DNA prevalence of 0.9%, which is comparable with other studies in blood donors demonstrating a PBV19 DNA prevalence ranging from 0.03‐1.3% . A United States study reported a PVB19 DNA prevalence of 0.88% with low PVB19 DNA viral loads ranging from 20‐1869 IU/ml .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation